Trauma cranioencefálico em pequenos animais - Siqueira, Emerson Gonçalves Martins [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Due to the importance of traumatic brain injury (TBI) in small animals, this paper aimed to discuss the pathophysiology of the TBI, the pre-hospital and hospital therapeutic procedures, as well as considerations related to transport and initial care of the patient immediately after trauma. The professional must identify the pre-hospital TBI and to treat the victim as a polytraumatized patient, including immobilization. In hospital therapy the procedures of craniotomy are important, especially to remove blood clots. In addition, the use of glucocorticoids must be avoided because of side effects, but combination therapies such as mannitol with furosemide increase the probability of success

Devido à importância do trauma cranioencefálico (TCE) em pequenos animais, o presente trabalho teve por objetivos discorrer sobre a fisiopatologia do TCE, os procedimentos terapêuticos pré-hospitalares e hospitalares, além de considerações relacionadas aos cuidados no transporte e manejo inicial do paciente imediatamente após o trauma. O profissional deve identificar o TCE pré-hospitalar e tratar o paciente como um indivíduo politraumatizado, incluindo os cuidados com a imobilização. Na terapia hospitalar os procedimentos de craniotomia são importantes, sobretudo para retirada de coágulos. Além disso, o uso de glicocorticóides precisa ser evitado devido aos efeitos secundários; por outro lado, associações terapêuticas como a do manitol com a furosemida aumentam as perspectivas de sucesso
Keywords: Veterinária de pequenos animais; Cranio; Traumatismos cerebrais; Head trauma; Multiple trauma; Small animals